THE EFFECTIVENESS OF AUDIO LINGUAL METHOD IN THE TEACHING OF SPEAKING AT SECOND GRADE OF SMPN 1 SEMEN - Ayuningtyas, Yuniarti; Setyawati, Lely (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 2 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research was carried out to answer the four statements of the problems. Those are (1) to describe the students’ speaking ability of the second year students in SMPN 1 Semen before being taught by using audio lingual method, (2) to describe the students’ speaking ability of the second year students in SMPN 1 Semen after being taught by using audio lingual method, (3) to find whether there is any significant difference between the second year students’ ability of SMPN 1 Semen before and after being taught by using audio lingual method, (4) to know whether using Audio lingual teaching method is effective to improve speaking ability for the second year student of SMPN 1 Semen. The school which becomes the subject of the research is SMPN 1 semen. The research design in this research was quantitative experimental design. The data of this study is collected by test and to know the effectiveness of using audio lingual method toward students’ speaking ability, the data analyzed by using t test. The subject is limited in class VIII-G (38) students. This research used tests only. The test that was used is pre-test and post-test. After getting the data, this result was calculated to answer the question whether using Audio Lingual method toward students’ speaking ability is effective or not. The results of this research can be concluded that the Audio Lingual method effective toward speaking ability of second grade grade at SMPN 1 Semen. Thus it is recommended (1) for the teacher to use the Audio Lingual method in teaching speaking, (2) for the students it is recommended that they should be always spirit to study English (3) for next researcher, hopefully can become the reference to conduct the next research. Then, the researcher hopes that this research can be perfected in the content and result by the further researcher.